Lectina Codium isthmocladum 1 (CiL-1): Interações com N-glicanos explicam atividades antinociceptiva e anti-inflamatória em zebrafish adulto (Danio rerio). - Alves, Antônio Willame da Silva (2021)
Inflammation and oxidative stress are processes associated with different human diseases. They are treated using drugs that have several side effects. Seaweed are sources of potentially relevant natural compounds for use as a therapeutic treatment of these disorders. Lectins are able to reversibly interact with complex carbohydrates and modulate cell membrane glycosylated receptors through this interaction. This study aimed to determine the antinociceptive and anti-inflammatory potential of CiL-1 in adult zebrafish by modulation of TRPA1 through lectin-glycan binding. Nociception was induced by formalin, and inflammation was induced by carrageenan. ROS content was determined using DCFH-DA. Possible neuromodulation by TRPA1 channel was also evaluated by camphor pretreatment. CiL-1 was efficacious at all tested doses, revealing anti-nociceptive and anti-inflammatory effects in adult zebrafish. This galactose-binding lectin was also able to reduce the content of ROS in brain and liver. In silico analyses showed CiL-1 interactions with both ligands tested. Oligosaccharide-1 (LacNac2) presents the most favorable binding energy with the protein. The interaction occurs at 4 subsites as an extended conformation at the site. Oligosaccharide-2 (LacNac2-Sia) had a less favorable curved-shape interaction energy. Based on the predictions made for the oligosaccharides, a tetra-antenate putative glycan was schematically constructed, illustrating an interaction between TRPA1 N-glycan and CiL-1. This binding seems to be related to CiL-1 anti-inflammatory activity as result of receptor modulation.